Endoscopic retrograde appendicitis therapy in the management of chronic fecalith appendicitis in a patient with ulcerative colitis: The first human case report - Zulqarnain, Muhammad; Cui, Guangxing; Lyu, Wen; Huang, Haitao; Wang, Xia; Abdi, Hamse Mohamoud; Gu, Lingfei; Fang, Shijie; Liu, Fangzhou; Ling, Liqian (Frontiers in Immunology, 2023)
To assess the effectiveness of Endoscopic Retrograde Appendicitis Therapy (ERAT) as a new technique and method for chronic fecalith appendicitis complicated by active ulcerative colitis. We report an 46-year-old male patient was admitted with right iliac fossa pain, tenderness, and raised inflammatory markers. A computed tomography scan of his abdomen confirmed dilated appendix, which is considered chronic fecalith appendicitis combined with active ulcerative colitis. He was treated with Endoscopic Retrograde Appendicitis Therapy procedure. The patient recovered well after the ERAT procedure and was discharged from the hospital in 2 days. During the 10-months follow-up, there was no report of recurrence pain in his abdomen. In conclusion ERAT could be seen as a different approach and be favored as a safer and more effective option in treating UC patients with appendicitis, especially those who are later in their course of the disease. Because of the ERAT procedure, such cases can avoid surgery and surgical-related complications. Further research and more cases need to be carried out to prove the efficacy and effectiveness of ERAT in appendicitis combined with IBD.